Is rapid, long-term economic growth in Poland likely? - Leon Podkaminer (Transformation, Integration and Globalization Economic Research (TIGER), 2004)
There are good reasons to assume that in the longer term Poland's economic growth will be unimpressive at best. This pessimistic judgement, however, does not reflect a sceptical evaluation of Poland's potential, but rather an evaluation of the merits of the current international economic order. More particularly, it reflects a critical assessment of the perceptions dominating the economic policies of the EU and its major countries. 'The Polish problem' is part of a larger problem: the wrong course taken by the EU itself. That course, however, is consistent with the evolution of the global economy which began with the abolition of the Bretton Woods system. It is only to be hoped that at some time the current global trends will be reversed. Alles ist moeglich. Until then, however, growth in Poland - and in the EU - can be expected at best to be unspectacular.
Keywords: 330; Wirtschaftswachstum; EU-Mitgliedschaft; Polen